2003
DOI: 10.1046/j.1365-201x.2003.01162.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of intramuscular lipid in insulin resistance

Abstract: There is interest in how altered lipid metabolism could contribute to muscle insulin resistance. Many animal and human states of insulin resistance have increased muscle triglyceride content, and there are now plausible mechanistic links between muscle lipid accumulation and insulin resistance, which go beyond the classic glucose-fatty acid cycle. We postulate that muscle cytosolic accumulation of the metabolically active long-chain fatty acyl CoAs (LCACoA) is involved, leading to insulin resistance and impair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
177
1
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 220 publications
(188 citation statements)
references
References 134 publications
9
177
1
1
Order By: Relevance
“…The IMCL content, which in many [1][2][3][4] but not all studies [45,46] has been shown to be increased in insulin resistance, was also one focus of our experiments. The effects of TGRLs on insulin signalling and glucose homeostasis followed a time-dependent fashion.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The IMCL content, which in many [1][2][3][4] but not all studies [45,46] has been shown to be increased in insulin resistance, was also one focus of our experiments. The effects of TGRLs on insulin signalling and glucose homeostasis followed a time-dependent fashion.…”
Section: Discussionmentioning
confidence: 96%
“…high plasma levels of NEFAs, dyslipidaemia and pronounced postprandial lipaemia. A fourth lipid abnormality suggested to be a determinant of insulin resistance is the increase of intramyocellular lipid (IMCL) content in skeletal muscle [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…The accumulation of lipid in muscle and other tissues has been linked to the development of insulin resistance [35]. Previous work has shown that adiponectin increases fat oxidation in muscle and liver, and that AMP kinase appears to play a central role in the regulation of lipid metabolism by adiponectin [6,9,10].…”
Section: Discussionmentioning
confidence: 99%
“…12 Furthermore, there is also evidence that as chronic hyperglycemia develops, the oversupply of glucose could also, by inhibiting fatty acid oxidation, lead to the accumulation of intramyocellular lipid metabolites that further inhibit glucose uptake/metabolism and hence exacerbate the state of insulin resistance. [13][14][15] Since Randle's proposal in 1963 of a glucose-fatty acid cycle that embodies direct competition between substrates for mitochondrial oxidation, a plethora of mechanisms have been put forward to explain how fuel substrates could interfere with glucose disposal in skeletal muscle. 12,15 Particularly striking is that oversupply of each of the three main fuel substrates canFas depicted in Figure 1Fconverge towards the accumulation of triglycerides.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] Since Randle's proposal in 1963 of a glucose-fatty acid cycle that embodies direct competition between substrates for mitochondrial oxidation, a plethora of mechanisms have been put forward to explain how fuel substrates could interfere with glucose disposal in skeletal muscle. 12,15 Particularly striking is that oversupply of each of the three main fuel substrates canFas depicted in Figure 1Fconverge towards the accumulation of triglycerides. This can occur not only when the supply of circulating free fatty acid (FFA) is in excess of its oxidation, but also when the supply of amino acids or glucose exceeds the oxidation of these fuels, thereby resulting in the formation of malonyl-CoA which, by inhibiting carnitine palmitoyltransferase-1 (CPT-1), reduces the entry of long-chain fatty acyl-CoAs (FA-CoA) into mitochondrial b-oxidation.…”
Section: Introductionmentioning
confidence: 99%